Event-related functional MRI of awake behaving pigeons at 7T - Mehdi Behroozi (Nature Portfolio, 2020)
Functional magnetic resonance imaging (fMRI) is a powerful method to understand neural mechanisms of cognition but imaging of small animals can be challenging. The authors present an event-related fMRI platform to visualize the neural fundaments of perceptual and cognitive functions in awake birds.